Supply Chain Performance Measurement at XYZ Company Distribution Center Using SCOR 12 - David Prasetya; Anggoro Prasetyo Utomo; Marla Setiawati (Petra International Journal of Business Studies, 2024)
Recognizing the limitations of their current, subjective evaluation system focused solely on delivery, XYZ Company seeks to implement a more standardized and comprehensive approach to supply chain performance measurement. This research aims to evaluate the performance of XYZ Company's Distribution Center (DC) supply chain using the well-established Supply Chain Operations Reference (SCOR) model. SCOR provides a validated set of performance indicators, which will be further weighted using the Analytical Hierarchy Process (AHP) to reflect their relative importance to XYZ Company's specific goals. The Snorm De Boer method will then be employed to normalize the final score for each indicator.  A traffic light system will visually represent performance gaps, highlighting areas requiring immediate improvement. This research will analyze data from 27 key metrics across 2022 and 2023, providing a holistic picture of DC performance. While preliminary results indicate an overall "average" to "good" performance (69.54 and 70.08, respectively), further analysis will identify specific areas for improvement based on SCOR Best Practices. This research will ultimately propose practical solutions to enhance XYZ Company's overall supply chain efficiency and effectiveness.